Spectral properties of nanoporous SiO₂ matrices with polymethine dye molecules - Bezkrovnaya, O.N.; Pritula, I.M.; Plaksii, A.G.; Puzikov, V.M.; Gurkalenko, Yu.A.; Kachkovskiy, A.D.; Slominsky, Y.L.; Kanaev, A. (Functional Materials, 2014)
SiO₂ matrices with PM1, PM2 and PM3 polymethine dyes are synthesized. The dyes PM2 and PM3 are found to form H-aggregates and dimers, respectively, in aqueous solutions. PM1 dye forms neither H-aggregates nor dimmers due to peculiarities of its structure. The luminescence maximum of PM1 dye in the matrix is shown to be hypsochromically shifted with respect to that in the solution. A rigid structure of SiO₂ matrix suppresses rotation of PM1 dye molecules, that increases the lifetime of the excited states of the dye molecules by 1.6 times in comparison with the one in the solutions.